Penerapan Flipped Learning Materi Mikrobiologi Terintegrasi Learning Management System - Setyati, Retno Herrani (Jurnal Pendidikan Biologi undiksha, 2021)
AbstractThis research was applied research that aim to apply flipped learning of Microbiology material integrated with the Learning Management System in online lectures during the Covid 19 Pandemic. This research is applied to the Human Health Science course, both class A and class B, which is attended by 80 Biology Education Study Program students. 2019 and held from August to October 2020 in the Biology Education Study Program at Sanata Dharma University. The step of implementing flipped learning begins with preparing RPS, video explanation of lecture material using o-matic screencast, journal, virtual lab, practicum simulation video using filmix, quiz using quizizz, and assessment rubric. Furthermore, the material and media are linked to Moodle (belajar.usd.ac.id). The data analyzed in this study included assignment scores, quizzes, and online lecture evaluation results. The results of the research obtained were the value of the assignment in the form of analysis of 3 microbiology journals, the mean score for class A was 81.4 and class B was 71.7, while the average quiz score for class A was 79.2 and class B was 76.6. The results of the overall learning evaluation class A 3,4, while class B 3.5. The application of flipped learning on the integrated Microbiology Learning Management System material based on the results of the evaluation of learning is categorized as very good.Keywords: flipped learning, microbiology, learning management system